The politics of honour in the Greek cities of the Roman empire - Heller, Anna, 1972-; Nijf, Onno van, 1961- (Brill studies in Greek and Roman epigraphy, 2017)
The volume The Politics of Honour in the Greek Cities of the Roman Empire , co-edited by Anna Heller and Onno van Nijf, studies the public honours that Greek cities bestowed upon their own citizens and foreign dignitaries and benefactors. These included civic praise, crowns, proedria , public funerals, honorific statues and monuments. The authors discuss the development of this honorific system, and in particular the epigraphic texts and the monuments through which it is accessible. The focus is on the Imperial period (1st-3rd centuries AD). The papers investigate the forms of honour, the procedures and formulae of local practices, as well as the changes in local honorific habits that resulted from the integration of the Greek cities in the Roman Empire.